Kritik terhadap Eksistensialisme Ateistik tentang Penolakan Eksistensi Tuhan - Alim Roswantoro (Al-Jami'ah Research Centre, 2005)
The article describes the atheist existentialists’ concept of God, arguments of taking away God, and then tries to criticize their concepts and arguments. General account on existentialists’ concept of God, which is represented in Nietzsche’s statement on the death of God, begins the paper. The following part is about arguments in denying the existence of God, followed by some critiques of them. The criticism of Muhammad Iqbal, who is a Muslim existentialist, on atheistic existentialistic concept of God ends the thoroughly paper. The result of this research is that atheist existentialists understand God in anthropomorphic explanation; the relation between God and human is identical with that of human and human. Even though they denied the existence of God with the reason of determinism, their arguments implied a new determinism, and the freedom they struggled indicated pseudo freedom.